2015
DOI: 10.1002/hbm.22905
|View full text |Cite
|
Sign up to set email alerts
|

Brain functional correlates of emotion regulation across adolescence and young adulthood

Abstract: Few studies have examined the neural correlates of emotion regulation across adolescence and young adulthood. Existing studies of cognitive reappraisal indicate that improvements in regulatory efficiency may develop linearly across this period, in accordance with maturation of prefrontal cortical systems. However, there is also evidence for adolescent differences in reappraisal specific to the activation of "social-information processing network" regions, including the amygdala and temporal-occipital cortices.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 97 publications
(115 reference statements)
3
48
0
Order By: Relevance
“…Control participants represent a subsample of a larger group included in our previous study of emotion regulation (Stephanou et al , 2016). Controls were selected to match patients on the variables of age, gender, years of education and estimated IQ.…”
Section: Methodsmentioning
confidence: 99%
“…Control participants represent a subsample of a larger group included in our previous study of emotion regulation (Stephanou et al , 2016). Controls were selected to match patients on the variables of age, gender, years of education and estimated IQ.…”
Section: Methodsmentioning
confidence: 99%
“…These studies have primarily examined cognitive reappraisal of negative content, which is notable as a common target of cognitive-behavioral therapies in youth with affective disorders. Here, cross-sectional studies of TD youth show greater downregulation of negative affect with age [2628] (though see [29,30]), and independent of general cognitive ability [27]. …”
Section: Typical Development Of Neural Circuits Supporting Negative Ementioning
confidence: 99%
“…Specifically, greater cortical thinning of dorsolateral and ventrolateral PFC in early adolescence was associated with greater use of cognitive reappraisal strategies in late adolescence. While the fMRI literature on the development of emotion regulation and its relation to neurodevelopment in adolescence is relatively nascent, some initial studies have examined brain activity in adolescents and young adults during directed cognitive reappraisal while viewing emotional images (McRae et al, 2012; Stephanou et al, 2016). McRae et al, (2012) found linear age-related increases in activation in the left ventrolateral prefrontal cortex during cognitive reappraisal, a region previously implicated in appraisal among adults, across 10–22 year olds.…”
Section: Control and Regulation Of Affective Behavior: Form And Fumentioning
confidence: 99%
“…These results suggest an increase in the recruitment of cognitive control structures to accomplish cognitive reappraisal from early adolescence into early adulthood. Another study compared adolescents and adults to examine the neural correlates of emotional reactivity and reappraisal in response to aversive social imagery (Stephanou et al, 2016). Younger participants showed greater activation of temporal-occipital brain regions during reappraisal and weaker suppression of amygdala reactivity, with the latter considered to be a general correlate of successful reappraisal.…”
Section: Control and Regulation Of Affective Behavior: Form And Fumentioning
confidence: 99%